Answer:
The first graph is given as
![\begin{gathered} f\mleft(x\mright)=3^x \\ when\text{ x=0} \\ y=3^x \\ y=3^0 \\ y=1 \\ \left(0,1\right) \\ when\text{ x=1} \\ y=3^1 \\ y=3 \\ \left(1,3\right) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ltybmc0elips4vluq9snx2s99vytu6352w.png)
Hence,
The graph is given below as
The second equation is given below as
![f\mleft(x\mright)=\lparen(1)/(3))^x](https://img.qammunity.org/2023/formulas/mathematics/college/487arx14n5oczct7t75xn9rovpkgr00p5v.png)
![\begin{gathered} f\mleft(x\mright)=\operatorname{\lparen}(1)/(3))^x \\ when\text{ x=0} \\ f\mleft(x\mright)=\operatorname{\lparen}(1)/(3))^0 \\ f\mleft(x\mright)=1 \\ \lparen0,1) \\ \\ when\text{ x= 1} \\ f\mleft(x\mright)=\operatorname{\lparen}(1)/(3))^1 \\ f\mleft(x\mright)=(1)/(3) \\ \lparen1,(1)/(3)) \\ when\text{ x=-1} \\ f\mleft(x\mright)=\operatorname{\lparen}(1)/(3))^(-1) \\ y=3 \\ \left(-1,3\right) \end{gathered}]()
Hence,
The graph is given below as
The third function is given below as
![\begin{gathered} f\mleft(x\mright)=\left((2)/(3)\right?^x \\ when\text{ x=0} \\ y=\left((2)/(3)\right?^0 \\ y=1 \\ \left(0,1\right) \\ \\ when\text{ x=-1} \\ y=\left((2)/(3)\right?^(-1) \\ y=(3)/(2)=1.5 \\ \left(-1,1.5\right) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/qeqves8gmk1h76p46jobcz6rdng611u59w.png)
The graph is given below as
The fourth equation is given below
![\begin{gathered} f\mleft(x\mright)=4^x \\ when\text{ x=0} \\ y=4^0=1 \\ \left(0,1\right) \\ \\ When\text{ x=1} \\ y=4^1=4 \\ \left(1,4\right) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/trfkcrv5uf47orklkclqnnndfcjft0v4bh.png)
The graph is given below as
Hence,
The final answer is given in the image below as